“I Want to Become a Better Person, Not Only a Better Artist”. An interview with Andrei ŞERBAN by Eugenia SARVARI - SARVARI, Eugenia (Studia Universitatis Babeș-Bolyai Dramatica, 2018)
Andrei Șerban was born in Bucharest in 1943. In 1969, after graduating (in Radu Penciulescu’s directing class), he received a scholarship at La MaMa Theatre in New York, followed by an astonishing international career in theater and opera. He worked in more than forty countries. In the USA, he was associated with Robert Brustein’s American Repertory Theatre Company and worked in many famous theatres and Operas in New York, Seattle and Los Angeles. Back to Romania after 1989, he was the artistic and executive director of the National Theatre in Bucharest between 1990 and 1993, but his international career continued. His Fragments of a Greek Trilogy – Medea, at „La MaMa”, 1972; Electra, at the Sainte-Chapelle, in Paris, 1973; The Trojan Women, at „La MaMa”, 1974, reunited in a trilogy at „La MaMa” (1974) and, then, in 1990 at the National Theatre in Bucharest, are considered the most original staging of the Greek tragedy at the end of the 20th century. Between 1992 and 2018 he was Professor at Columbia University, New York. Many volumes were dedicated to his work as a stage director. He published the autobiographical volume O biografie (2007, Polirom).